2021
DOI: 10.1158/0008-5472.can-20-2629
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome and Cancer: Creating Friendly Neighborhoods and Removing the Foes Within

Abstract: The human body is colonized by the microbial cells that are estimated to be as abundant as human cells, yet their genome is roughly 100 times the human genome, providing significantly more genetic diversity. The past decade has observed an explosion of interest in examining the existence of microbiota in the human body and understanding its role in various diseases including inflammatory bowel disease, neurologic diseases, cardiovascular disorders, and cancer. Many studies have demonstrated differential commun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 145 publications
(140 reference statements)
0
32
0
Order By: Relevance
“…It is well recognized that microbiota can impact on gut and systemic host metabolism through several mechanisms such as the maintenance of gut barrier integrity, the ability to absorb energy from digested nutrients, the production of metabolites (i.e., short chain fatty acids (SCFAs), secondary bile acids, endotoxins) and gut-derived hormones (i.e., GLP-1, GIP, PPY) that affect satiety and/or peripheral insulin sensitivity, and the modulation of epigenetic modifications [ 278 ]. Therefore, it may come as no surprise that gut dysbiosis could be linked to various human diseases, including cancer, by influencing the genomic stability of host cells through the modulation of many different signaling pathways [ 279 ]. Previous studies have reported a correlation between low gut microbiota richness (i.e., low bacterial gene count) and metabolic dysfunction, including IR, dyslipidemia, excess adiposity, and inflammation [ 275 ].…”
Section: Gut Microbiota and Cancermentioning
confidence: 99%
“…It is well recognized that microbiota can impact on gut and systemic host metabolism through several mechanisms such as the maintenance of gut barrier integrity, the ability to absorb energy from digested nutrients, the production of metabolites (i.e., short chain fatty acids (SCFAs), secondary bile acids, endotoxins) and gut-derived hormones (i.e., GLP-1, GIP, PPY) that affect satiety and/or peripheral insulin sensitivity, and the modulation of epigenetic modifications [ 278 ]. Therefore, it may come as no surprise that gut dysbiosis could be linked to various human diseases, including cancer, by influencing the genomic stability of host cells through the modulation of many different signaling pathways [ 279 ]. Previous studies have reported a correlation between low gut microbiota richness (i.e., low bacterial gene count) and metabolic dysfunction, including IR, dyslipidemia, excess adiposity, and inflammation [ 275 ].…”
Section: Gut Microbiota and Cancermentioning
confidence: 99%
“…More recent research has highlighted the role of the local microbiome of the tumour microenvironments outside of the gut; for example, a Mediterranean diet has been shown to alter the microbiome of the breast by increasing the abundance of microbes, such as Lactobacillus, when compared to a western diet [79]. Further, studies have begun to identify a series of distinct tumour-specific microbiomes associated with select cancers [80][81][82], which can be associated with therapeutic response [83,84]. Understanding these distinct microbe profiles may allow for early detection in the future, or allow for preventative measures through microbe-altering therapies or dietary interventions.…”
Section: Microbes As Key Mediators In Diet−cancer Interactionsmentioning
confidence: 99%
“…Numerous studies have shown altered gut microbioata composition during the development of various cancers including but not limited to colorectal cancer (Nakatsu et al, 2015), gastric cancer (Ferreira et al, 2018), lung cancer (Zhuang et al, 2019), pancreatic cancer (Half et al, 2019), prostate cancer (Daisley et al, 2020), breast cancer (Goedert et al, 2015), brain cancer (D'Alessandro et al, 2020) and even leukemia (Vicente-Dueñas et al, 2020). Mechanistically, the gut microbiome can influence tumorigenesis at sites distant to the gut by regulating circulatory levels of metabolites and nutrients as well as through the release of microbial toxins which are currently under intense investigation (Parida and Sharma, 2021). Changes in the gut microbiota community has also been documented in the pathogenesis of age-related cardiovascular disorders such as heart failure and coronary artery diseases.…”
Section: Gut Microbiota In Aging and Associated Diseasesmentioning
confidence: 99%